MEKANISME DAN REGULASI PENEGAKAN HUKUM TERHADAP STREAMER GAME YANG MENYAMPAIKAN INFORMASI TENTANG JUDI ONLINE DI YOUTUBE - Gunadi, I Made Dwi Artha; Sugiantari, Anak Agung Wiwik (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Streamer game who disseminate information about online gambling platforms during live streaming share similar mechanisms with influencers such as celebrities, content creators, and artists who endorse online gambling platforms. However, the legal enforcement differs between them. This thesis explores the legal enforcement against game streamers disseminating information about online gambling via YouTube in Kabupaten Badung, covering legal foundations, enforcement procedures, forms of legal enforcement, influencing factors, and conflict resolution mechanisms. The research aims to understand the mechanisms and procedures of legal enforcement, forms of legal enforcement, and influencing factors. It employs empirical legal research with a factual and sociological approach, utilizing data from interviews with key informants and questionnaire distribution. The collected data will undergo qualitative processing and analysis. The study draws upon several theories, including legal system theory, law enforcement theory, and legal effectiveness theory. Findings indicate deficiencies in government efforts to prevent this issue and disparities in legal enforcement